Resposta imune humoral e celular a Blomia tropicalis e sua fração ligante de Concanavalina A em pacientes atópicos - Alves, Ronaldo (2007)
Blomia tropicalis (Bt), Dermatophagoides pteronyssinus (Dp) and D. farinae (Df) are the prevalent house dust mites (HDMs). Concanavalin A-binding components derived from B. tropicalis (Bt-ConA extract) have shown to be highly immunogenic in allergic diseases. This study aimed to evaluate the humoral and cellular immune responses to B. tropicalis in sensitized patients. A total of 246 subjects aged 18 and 60 years were selected for this study. Among them, 137 (54 male and 83 female) had allergic rhinitis with or without asthma and 109 (37 male and 72 female) were non-atopic subjects. All subjects were tested for skin reactivity (SPT), total serum IgE and specific IgE levels to both Bt-total and Bt-ConA extracts, proliferative response and cytokine (IFN-γ and IL-5) production by peripheral blood mononuclear cells (PBMC) stimulated with both extracts. SPT showed that 70% of patients were sensitized to Bt (Bt+) and no patient was monosensitized to Bt. Similar levels of specific IgE to Bt-total and Bt-ConA extracts were found in Bt+ patients, while higher levels of total serum IgE were found in atopic than non-atopic subjects. Significant PBMC proliferation was observed in response to Bt-total extract in Bt-sensitized, but not in Bt-non-sensitized patients and non-atopic subjects. Bt-ConA extract induced increased proliferative responses in all patient groups, but these responses were decreased in the presence of ConA inhibitor (methyl-α-D-mannopyranoside). Significant IFN-γ production was observed only after Bt-ConA stimulation in Bt+ patients, while Bt-total extract showed no changes. IL-5 production was consistently seen in Bt+ patients after allergen-specific stimulation or even with no stimulus, indicating that PBMC from allergic patients are prone to produce spontaneously or allergen-restimulation induced Th2-type cytokines. It can be concluded that the Bt-total extract contains relevant allergens that are involved in both humoral and cellular immune responses, while the Bt-ConA extract containing glycosilated components associated with ConA residues might be an important inducer of Th1 immune response and therefore, to present a potential use in immunotherapeutic procedures.